2014
DOI: 10.1103/physrevlett.112.163902
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of High-Order Scattering Processes in Ultrasmall Optical Resonators to Control Far-Field Emission

Abstract: By imposing a set of harmonic perturbations to a microcavity boundary, we induce conversion and mixing of orbital angular momentum of light via surface scattering. Multiple scattering paths are available due to high-order scattering, which can be greatly enhanced by quasidegenerate resonances. By manipulating the relative strengths of these scattering processes, we theoretically synthesize the angular momentum spectra of individual modes so as to control their far-field patterns. We demonstrate experimentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…has additional WG waves of higher radial order number 7 and azimuthal number 34. This is attributed to the mixing of WG modes with different order via wave scattering by the rough boundary of the microdisk [32][33][34].…”
Section: Theoretical Analysis Of Lasing Mode Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…has additional WG waves of higher radial order number 7 and azimuthal number 34. This is attributed to the mixing of WG modes with different order via wave scattering by the rough boundary of the microdisk [32][33][34].…”
Section: Theoretical Analysis Of Lasing Mode Selectionmentioning
confidence: 99%
“…In practice, there is always inherent cavity surface roughness introduced unintentionally during the fabrication process. The coupling between high-Q WG modes of low radial numbers and lower-Q WG modes of higher radial numbers, caused by the surface roughness [32][33][34], enhances the spatial diversity of the lasing WG modes, which plays a critical role to differentiate the WG modes by adaptive pumping.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the underlying mechanism of the coupling of modes with different angular momenta in a weakly deformed microdisk cavity is ascribed to the surface scattering processes of light at the microcavity sidewall, of which the strengths can be individually evaluated for different scattering paths by the perturbation theory. [64,65] In fact, the scattering processes are not limited to weakly deformed microdisk cavities, i.e., the formation and characteristics of modes in strongly deformed microdisk cavities are also governed by the scattering. [10] The scattering processes can be manipulated by imposing specific cavity shape deformation to achieve unidirectional light emission for weakly deformed microdisk cavities, according to the perturbation theory.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The scattering processes can be manipulated by imposing specific cavity shape deformation to achieve unidirectional light emission for weakly deformed microdisk cavities, according to the perturbation theory. [55,65] In general, the coupling of modes with different angular momenta via surface scattering processes is in the weak coupling regime for weakly deformed microdisk cavities, as the scattering processes are trivial non-resonant scattering. [55,64] However, the coupling of modes is radically altered in quasi-degenerate cases, where resonant scattering processes occur.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It has been shown that a smooth deformation from circular symmetry produces directional light output. [8][9][10][11][12][13][14][15] Usually, these cavities are pumped uniformly, and lasing occurs in the modes with the highest-Q values. These modes are generally whisperinggallery like and reside close to the cavity boundary.…”
mentioning
confidence: 99%